Penguatan Karakter Remaja Melalui Edukasi Seks Bebas Berbasis Puzzle Interaktif - Desi Nindya Kirana; Penika Vaiza; Nabila Syahfitri; Ariana Ariana; Sindy Aptia Ningsih (Jurnal Medika: Medika, 2025)
The high number of cases of promiscuity among adolescents demonstrates the need for an educational approach that not only conveys information but also fosters strong and responsible character. Adolescents require learning media that is fun, interactive, and addresses both cognitive and affective aspects simultaneously. The purpose of this activity was to develop and evaluate interactive puzzle media that combines promiscuity education with the strengthening of character values, such as responsibility, integrity, and self-esteem. The methods used were Socialization, Counseling, SGD, and Evaluation (interactive puzzle media). This activity involved 35 junior high school students as respondents. The intervention was carried out through educational puzzle sessions specifically designed to help adolescents understand the risks of promiscuity and reflect on adolescent choices and moral values. Interactive puzzle media was used to assess adolescents' knowledge and character aspects before and after the intervention. The results showed that the use of interactive puzzle media was proven effective in increasing adolescents' knowledge about the risks of promiscuity while strengthening character values such as responsibility, integrity, and self-esteem. This media has the potential to be an alternative interactive learning method that can be used sustainably in schools.